2000
DOI: 10.1103/physrevb.61.7253
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parallel magnetic fields on a single-layer two-dimensional electron system with a hopping mechanism of conductivity

Abstract: Large positive (P) magnetoresistance (MR) has been observed in parallel magnetic fields in a single 2D layer in a delta-doped GaAs/AlGaAs heterostructure with a variable-range-hopping (VRH) mechanism of conductivity.Effect of large PMR is accompanied in strong magnetic fields by a substantial change in the character of the temperature dependence of the conductivity. This implies that spins play an important role in 2D VRH conductivity because the processes of orbital origin are not relevant to the observed eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…The temperature dependence of the resistivity in zero field was attributed to Efros-Shklovskii variable range hopping with α = 1 2 down to ≈ 0.3 K by Mertes et al [11] and Jarozynski et al [13] and over a broader range to lower temperatures by Mason et al [22]. The zero-field resistivity was found to obey the same form in a single two-dimensional layer of δ-doped GaAs/Al x Ga 1−x As [25]. By contrast, Arrhenius-type activated behavior (α = 1) was claimed for silicon in zero field by Shashkin et al [12].…”
Section: Fig 1: Nonlinear Current-voltage (I-v) Characteristics In Zeromentioning
confidence: 86%
See 1 more Smart Citation
“…The temperature dependence of the resistivity in zero field was attributed to Efros-Shklovskii variable range hopping with α = 1 2 down to ≈ 0.3 K by Mertes et al [11] and Jarozynski et al [13] and over a broader range to lower temperatures by Mason et al [22]. The zero-field resistivity was found to obey the same form in a single two-dimensional layer of δ-doped GaAs/Al x Ga 1−x As [25]. By contrast, Arrhenius-type activated behavior (α = 1) was claimed for silicon in zero field by Shashkin et al [12].…”
Section: Fig 1: Nonlinear Current-voltage (I-v) Characteristics In Zeromentioning
confidence: 86%
“…For a single two-dimensional layer of δ-doped GaAs/Al x Ga (1−x) As in parallel fields of 8 T and 6 T, Shlimak et al reported an exponent of 0.8 [25].…”
Section: Fig 1: Nonlinear Current-voltage (I-v) Characteristics In Zeromentioning
confidence: 99%
“…The strong positive MR persists deep in the insulating state and is exhibited by systems which were perfectly insulating at H ¼ 0 [4]. The temperature dependence of the MR is close to the Arrhenius law even if for H ¼ 0 the system exhibits a variable range hopping of Efros-Shklovskii type (such a behavior was observed for Si MOS-FETS [4] and n-type GaAs heterostructures [15]). As we have discussed earlier, the activated behavior of MR in the hopping regime can be a signature of the hopping over the states of the UHB.…”
mentioning
confidence: 78%
“…Measurements were made on two silicon MOSFET's of mobility approximately 20 000 V/cm 2 at 4.2 K using a gate to control electron densities between 0.64ϫ10 11 cm Ϫ2 and 3.60ϫ10 11 cm Ϫ2 . Contact resistances were minimized by using a split-gate geometry that allows a higher electron density in the vicinity of the contacts than in the 2D system under investigation.…”
mentioning
confidence: 99%
“…We now briefly consider the behavior of the resistance in high fields for electron densities above 1.35ϫ10 11 …”
mentioning
confidence: 99%